Leaflet - Horsham and District Trades and Labour Council, 9 May 1926 (Horsham)
1926-05-09 "Leaflet - Horsham and District Trades and Labour Council, 9 May 1926" [g0280001.jpg], 9 May 1926 Local Organisation